2013
DOI: 10.1017/s0952523813000588
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of voltage-gated Ca2+ channels in rat retinal ganglion cells by gabapentin

Abstract: The α2δ auxiliary subunits of voltage-gated Ca2+ channels (VGCCs) are important modulators of VGCC function. Gabapentin interacts with α2δ1 and α2δ2 subunits and is reported to reduce Ca2+ channel current amplitude (ICa). This study aimed to determine the effects of gabapentin on VGCCs in retinal ganglion cells (RGCs). Whole cell patch clamp was used to record ICa in isolated RGCs, and calcium imaging was used to measure Ca2+ transients from RGCs in situ. Immunohistochemistry was used to detect the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It is possible that the function of α2δ4 in cones is redundant with another, cone-specific α2δ member, which compensates partially for its loss. Indeed, the presence of other α2δ isoforms in the photoreceptor synaptic layer has been documented (Farrell et al, 2014; Perez de Sevilla Muller et al, 2015). Alternatively, cones may use different molecular mechanisms for synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the function of α2δ4 in cones is redundant with another, cone-specific α2δ member, which compensates partially for its loss. Indeed, the presence of other α2δ isoforms in the photoreceptor synaptic layer has been documented (Farrell et al, 2014; Perez de Sevilla Muller et al, 2015). Alternatively, cones may use different molecular mechanisms for synaptogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the network was enriched in transmembrane ion transporters. This included several calcium- and sodium-gated channel subunits, all of which have been previously localized to RGCs (Lipton and Tauck, 1987 ; Farrell et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As was shown in the immunofluorescence assay, the immunofluorescence intensity of α2δ-1 in the GBP group was weaker than in the 12 h group ( Fig 9D ). This indicated that GBP could effectively decease the cell surface expression of α2δ-1 so that GBP could block the interaction of TSP2 with α2δ-1[ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the cultures were washed 3 times as described above and incubated with Alexa-conjugated secondary antibodies (1:500, Jackson Immuno Research, West Grove, PA, USA) for 2 h. After washing three times in PBS, the cultures were covered with Vectashield mounting medium containing DAPI (Vector Laboratories, Burlingame, USA). The cells immunostained with the α2δ-1 antibody were not permeabilized with Triton-X to limit antibody staining to the cell surface[ 35 ]. For immunofluorescence intensity analysis, all the cell cultures were stained simultaneously under the same setting.…”
Section: Methodsmentioning
confidence: 99%